2006
DOI: 10.1111/j.1365-2265.2006.02701.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin does not regulate the GH response to insulin‐induced hypoglycaemia in children but could be involved in the regulation of cortisol secretion

Abstract: This study shows that ghrelin might not regulate the GH response to insulin-induced hypoglycaemia in prepubertal and pubertal children. A role for ghrelin in the regulation of cortisol secretion can be hypothesized concerning the negative correlation between changes in ghrelin and cortisol. Furthermore, the results imply that ghrelin secretion is age dependent and is a function of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
6
1
4
Order By: Relevance
“…However, it still remains to be elucidated which factor ultimately controls this stimulation of GH release in response to stress. Previous insulin tolerance test studies on total and acylated ghrelin demonstrated that insulin-induced hypoglycemia did not suppress the ghrelin secretion and GH might not be regulated by ghrelin [17][18][19]. In our study, GH levels were elevated whereas total ghrelin levels were decreased, and the total ghrelin levels were lower in the subjects with inhalation burn compared with the subjects without inhalation injury.…”
Section: Discussioncontrasting
confidence: 72%
“…However, it still remains to be elucidated which factor ultimately controls this stimulation of GH release in response to stress. Previous insulin tolerance test studies on total and acylated ghrelin demonstrated that insulin-induced hypoglycemia did not suppress the ghrelin secretion and GH might not be regulated by ghrelin [17][18][19]. In our study, GH levels were elevated whereas total ghrelin levels were decreased, and the total ghrelin levels were lower in the subjects with inhalation burn compared with the subjects without inhalation injury.…”
Section: Discussioncontrasting
confidence: 72%
“…Other markers pointing to mechanisms devoted to regulation of calf size (16 SNP markers spanning from 51821819 to 74823222 bp) were identified on chromosome 5, corresponding to regions previously mapped for birth weight (Schrooten et al 2000;Casas et al 2003) and calving ease (Schrooten et al 2000) in the proximity of the IGF1 gene (NCBI NM_001077828.1), and on chromosome 19, where significant SNPs with large B-LOD scores in both US-HOL and ITA-BS populations are located (Table 4). Furthermore, it has also been recently linked to the regulation of cortisol levels and stress response (Huber et al 2007). In this regard, a significant region lies between SNPs ARS-BFGL-NGS-31598 (30093999 bp) and ARS-BFGL- NGS-19878 (35925392 bp), including the GHR (NCBI NC_007318.4) gene.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings have suggested that ghrelin may play a role in the control of food intake and meal frequency as well as energy intake [36]. Specifically ghrelin in the plasma increases preprandially in fasting conditions and before meal initiation and will rapidly decrease nadir postprandially [37] and therefore is reported to play a role in appetite regulation, meal frequency, and hunger [36]. Solomon et al [32] have suggested that a larger preprandial surge in ghrelin may occur with larger and less frequent meals that could cause more meal initiation and more between-meal snacks.…”
Section: Meal Frequencymentioning
confidence: 99%
“…One study [36] reported that cortisol levels correlated negatively with ghrelin suggesting that cortisol may peak after ingestion of a meal and return to nadir some time after meal completion. Hypercortisolism in another study [45] suppressed ghrelin levels.…”
Section: Meal Frequencymentioning
confidence: 99%
See 1 more Smart Citation